الاطار القانوني لبيع حصص التلوث-دراسة تحليلية في ضوء بروتوكول اتفاقية كيوتو بشأن الاحتباس الحراري وتغير المناخ - سليمان الأحمد, محمد; صالح عبد الكريم, عبد الكريم (revue mofakir; No 12 (2015): مجلـــة المفكــر, 2018)
‫‪‫‪The‬‬ ‫‪Kyoto‬‬ ‫‪protocol‬‬ ‫‪is‬‬ ‫‪an‬‬ ‫‪international‬‬ ‫‪treaty‬‬ ‫‪GHG‬‬ ‫‪emissions‬‬ ‫‪blamed‬‬ ‫‪for‬‬ ‫‪global‬‬ ‫‪warming,‬‬ ‫‪the‬‬ ‫‪protocol‬‬ ‫‪was‬‬ ‫‪been‬‬ ‫‪in‬‬ ‫‪force‬‬ ‫‪in‬‬ ‫‪2005‬‬ ‫‪and‬‬ ‫‪it‬‬ ‫‪is‬‬ ‫‪signed‬‬ ‫‪by‬‬ ‫‪141‬‬ ‫‪counties.‬‬ ‫‪According‬‬ ‫‪to‬‬ ‫‪the‬‬ ‫‪protocol‬‬ ‫‪each‬‬ ‫‪country‬‬ ‫‪makes‬‬ ‫‪emission‬‬ ‫‪carbon‬‬ ‫‪reduction‬‬ ‫‪by‬‬ ‫‪any‬‬ ‫‪project,‬‬ ‫‪has‬‬ ‫‪a‬‬ ‫‪right‬‬ ‫‪to‬‬ ‫‪sell‬‬ ‫‪their‬‬ ‫‪carbon‬‬ ‫‪credits‬‬ ‫‪which‬‬ ‫‪provided‬‬ ‫‪by‬‬ ‫‪clean‬‬ ‫‪development‬‬ ‫‪mechanism‬‬ ‫‪and‬‬ ‫‪international‬‬ ‫‪emission‬‬ ‫‪trading‬‬ ‫‪in‬‬ ‫‪united‬‬ ‫‪nation‬‬ ‫‪to‬‬ ‫‪another‬‬ ‫‪country‬‬ ‫‪which‬‬ ‫‪need‬‬ ‫‪it‬‬ ‫‪because‬‬ ‫‪of‬‬ ‫‪its‬‬ ‫‪high‬‬ ‫‪commercial‬‬ ‫‪and‬‬ ‫‪industrial‬‬ ‫‪act.‬‬ ‫‪This‬‬ ‫‪research‬‬ ‫‪is‬‬ ‫‪aimed‬‬ ‫‪to‬‬ ‫‪study‬‬ ‫‪the‬‬ ‫‪legal‬‬ ‫‪nature‬‬ ‫‪of‬‬ ‫‪contract‬‬ ‫‪subject‬‬ ‫‪and‬‬ ‫‪the‬‬ ‫‪situation‬‬ ‫‪of‬‬ ‫‪Iraqi‬‬ ‫‪law‬‬ ‫‪and‬‬ ‫‪comparative‬‬ ‫‪law‬‬ ‫‪about‬‬ ‫‪this‬‬ ‫‪kind‬‬ ‫‪of‬‬ ‫‪contracts.‬‬